Beyond individual differences : organizing processes, information overload, and classroom learning - Ahern, Charles A. (Springer New York, 2012)
In an era of intense interest in educational reform, spurred by increasing global competition for jobs and advancement, it is more critical than ever to understand the nature of learning. And although much attention is paid to differences between learners, short shrift is often given to cognitive functions that characterize successful learning for all students. Yet these are the very functions that determine the difference between successful and rewarding learning versus merely "doing" without truly learning.  Firmly grounded in the principles of neuropsychology, Beyond Individual Differences analyzes both successful and unproductive learning in terms of the brain's organizing processes - that is, its unconscious sifting, selecting, and meaning-making that enable students to incorporate and build on what they've learned in the past. At the same time, it explores the learning situations that cause organization to break down and offers several preventive strategies. Key areas of coverage include:  The complex role of mental organization in learning and education. Specific organizing processes and the links to success or failure in learning. Information/cognitive overload. The student's experience of learning and its impact on development. Accommodating a range of individual differences in the classroom. Practices for supporting students' unconscious organizing processes. Beyond Individual Differences is essential reading for a wide range of professionals and policy makers as well as researchers and graduate students in school and clinical child psychology, special and general education, social work and school counseling, speech therapy, and neuropsychology. ----- Beyond Individual Differences is an important book. Speaking directly to the classroom setting, it addresses essential issues concerning what it means to learn and what it means to teach. This work represents a significant step in furthering the collaboration between the fields of neuropsychology, school psychology, and education.   Karl H. Pribram, M.D., Ph.D. Distinguished Professor of Neuroscience at Georgetown and George Mason Universities, Emeritus professor of psychology and psychiatry at Stanford University and Radford University Winner of the Dagmar and Vaclav Havel Prize, and the Noetic Medal of Consciousness and Brain Research